2003
DOI: 10.1051/0004-6361:20021562
|View full text |Cite
|
Sign up to set email alerts
|

Fast-rotating nearby solar-type stars

Abstract: Abstract. We present an analysis of our high-resolution spectroscopic and high-precision UBV(RI) c photometric observations of a sample of 110 nearby late-F and G-type stars selected for their large rotational velocity. The relationships between Li abundance, X-ray luminosity, and v sin i are investigated. We find that, as expected, the stars in our sample show statistically higher Li abundance and activity level than field star samples with similar characteristics, but slower rotation. Surprisingly, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…Neither of these algorithms shows a solution with a high power and the most likely periods differ when deleting 20% of data randomly. This suggests that apart from the brightness variation of HD 102077 due to stellar activity as has also been seen in the shorter period observations (Cutispoto 1990(Cutispoto , 1993(Cutispoto , 1998 no other signal can be detected in the H data.…”
Section: V-band Variabilitysupporting
confidence: 58%
See 1 more Smart Citation
“…Neither of these algorithms shows a solution with a high power and the most likely periods differ when deleting 20% of data randomly. This suggests that apart from the brightness variation of HD 102077 due to stellar activity as has also been seen in the shorter period observations (Cutispoto 1990(Cutispoto , 1993(Cutispoto , 1998 no other signal can be detected in the H data.…”
Section: V-band Variabilitysupporting
confidence: 58%
“…The photometric determination of the metallicity content is not very accurate because of HD 102077s binarity and variability and this may be the cause of the discrepancy. For instance, Cutispoto (1990) measured the U BVRI colours over several photometric phases A&A 564, A10 (2014) and observed that U − B varies by 0.04 mag and that the star gets bluer at light maximum. Even stronger variations have been observed by Udalski & Geyer (1985).…”
Section: Introductionmentioning
confidence: 99%
“…Since a light curve represents one-dimensional time series the resulting stellar image contains information on the spot distribution only in one direction, in longitude, while spot extents and locations in latitude remain uncertain. However, because of the projection effect and limb darkening, light-curve inversion images show better-defined structures than the light curves themselves and, therefore, can be used to determine longitudes of spot Rucinski (1983) 3 4 44 982-44 993 74 Rucinski (1983) 4 3 45 249-45 266 180 Kubiak (1985) 3 45 791 43 Innis et al (1988) 3 9 46 019-46 020 18 Innis et al (1988) 3 9 46 040-46 050 745 Lloyd 46 043-46 055 614 Jetsu et al (1990) 3 4 46 096-46 097 40 Innis et al (1988) 3 9 46 389-46 397 23 Cutispoto & 3 5, 6 Rodonò (1988) 46 445-46 446 14 Innis et al (1988) 3 9 46 520-46 521 29 Innis et al (1988) 3 9 46 703-46 704 100 Innis et al (1988) 3 9 46 736-46 743 107 Kubiak et al (1995) 3 46 756-46 841 42 Cutispoto (1990) 3 5 46 810-46 811 64 Innis et al (1988) 3 9 47 548-47 595 60 Kürster et al (1994) Bos (1994b) 3 11 49 311-49 323 34 Unruh et al (1995) 5 2 49 317-49 327 20 Anders (1994) 3 9 49 659-49 724 708 Budding et al (1995) concentrations. Although this approach is less informative than the Doppler imaging technique, the analysis of long series of photometric observations allows us to recover longitudinal spot patterns and study their long-term evolution.…”
Section: Light Curve Inversionsmentioning
confidence: 99%
“…In the α Per cluster, more rapid rotators also appear to have a stronger lithium abundance (Balachandran et al 1988;Stauffer et al 1993). These results are the same for nearby field solar-type stars (de Medeiros et al 2000;do Nascimento et al 2000;Cutispoto et al 2003). On the other hand, observations and data analysis show that the rapid rotation of young solar-type stars exhibits higher X-ray luminosity Xing et al 2007a).…”
Section: Discussion and Resultsmentioning
confidence: 74%